Práticas de governança pública e efetividade do enfrentamento da Covid-19 nos municípios do Paraná - Cezar, Gislaine Siebre (2022)
The research seeks to verify the influence of public governance practices on the effectiveness of coping with covid-19 in the municipalities of Paraná. For this, it identified a set of public governance practices in the municipalities of Paraná, through indices, and related them to the fight against covid-19. The public governance indices used for the analysis are: IEGM, IFDM, IFGF, IGM-CFA, ITP/TCEPR and ITP-Covid-19. To structure the indicator in the fight against covid-19, it used the number of accumulated cases and deaths registered until December 2021. The methodological procedures were carried out in three stages: the first is based on data collection, through documentary research, the second performed using descriptive statistics to analyze the variables, finally, two regression models were made, one to explain accumulated cases of covid-19 and the other to explain the accumulated deaths due to covid-19. In the descriptive and comparative analysis, the effectiveness of public governance in dealing with covid-19 in the municipalities of Paraná cannot be confirmed, because, contrary to what was expected, the relationship between the variables is positive. When segregating the data by health regional, it is noted that there is no correlation between public governance and the number of cases and accumulated deaths, however, in the 399 observations, it appears that the number of cases and accumulated deaths showed a statistically positive association and significant with all public governance indices. In the statistical analysis of the linear regression models, it was found that of the six public governance indices, only three indices, IGM-CFA, IFDM and IEGM, have a positive and statistically significant impact on both models. In this way, good municipal management practices (IGM), the effectiveness of municipal public policies (IEGM) and socioeconomic development of municipalities (IFDM) have a positive and significant impact on the number of cases and deaths accumulated by covid-19.